Sistem Pendidikan Dayah Dalam Membangun Karakter Santri - Syadidul Kahar (Pusdikra Publishing, 2021)
Dayah is a traditional Islamic educational institution in Aceh that gave birth to scholars to enlighten the people. Today's developments require dayah to continue to exist, giving generations of morals. This research is a qualitative research with a social history approach. The findings concluded that basically the community's anxiety due to the dominance of materialism which makes the soul arid, has provided opportunities for people to look for institutions. The modernization that has been carried out is still based on the original tradition, which is based on dayah with a modern twist so that the dayah is MUDI. The modernization of the dayah education system during the Abon Abdul Aziz era included modernizing the curriculum, facilities and infrastructure and modernizing learning methods. The purpose of this change is so that the dayah will continue to exist in this era of globalization so that the vision of giving birth to scholars is still running. The dayah education system managed by Abon Abdul Aziz remains in control to shape the morals of thalabah so that the knowledge obtained in the dayah is still used in terms of goodness. Through the touch of moral education to the talabah who studied in the dayah, most of the istiqamah studied until they got permission from Abon Abdul Aziz to practice their knowledge in the community.